THE IMPACT OF THE USE OF TECHNOLOGY ON SOCIAL INTERACTION IN COMMUNICATION SCIENCE DEPARTMENT STUDENTS SEMESTER VI STATE ISLAMIC UNIVERSITY OF NORTH SUMATERA - Syalwa, Jihan; Mzuhaffar, Muhammad Hanif; Annisa Fadillah (OPINI: Journal of Communication and Social Science, 2024)
The study highlights the positive impacts of technology use, including easier access to information, maintaining communication with friends who live far away, broadening knowledge, and supporting academic communication and learning. However, negative effects also occur, such as a decline in the quality of personal communication, limited nonverbal communication skills, poor academic concentration, and dependence on technology for social interaction. It is recommended to manage technology use wisely in campus environments, enhance digital awareness, and encourage activities that require face-to-face communication such as group discussions and collaborative projects to help students develop social skills and build better interpersonal relationships.